SPACE FAULT TREE THEORY AND SYSTEM RELIABILITY ANALYSIS - Cui, Tie Jun (Current Natural Sciences Ser., 2020)
The significance of the existence of the system is to realize its function and maintain its stability, that is, the reliability and stability of the reliability. Reliability is affected by factors, component properties and system structure, and its changes are complex. In order to solve this problem, the authors proposed the space fault tree theory in 2012. This book is the first time that the fundamental part of the theory has been presented internationally. The authors of the book are Pro. Tiejun Cui and Dr. Shasha Li. Tiejun CUI was born in Shenyang, Liaoning, China in 1983. He received a Ph.D. degree in safety technology and engineering from Liaoning Technical University, China in 2015, and received two postdoctoral degrees. His research interests include safety system engineering, system reliability and system fault evolution processes. He is the author of several books and author and co-author of several publications in international journals, including papers that are indexed by SCI and EI. Shasha LI was born in Panjin, Liaoning, China, in 1988. She received a Ph.D. degree in safety management engineering from Liaoning Technical University, China in 2018. Her research interests include safety management engineering and system reliability. She is the author and co-author of several publications in International journals and Chinese journals and books, including papers that are indexed by SCI and EI.